2017
DOI: 10.1016/j.robot.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Control, localization and human interaction with an autonomous lighter-than-air performer

Abstract: Due to the recent technological progress, Human-Robot Interaction (HRI) has become a major field of research in both engineering and artistic realms, particularly so in the last decade. The mainstream interests are, however, extremely diverse: challenges are continuously shifting, the evolution of robot skills, as well as the advances in methods for understanding their environment radically impact the design and implementation of research prototypes. When directly deployed in a public installation or artistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…An important issue for the supervision of a semiautonomous swarm is the possibility to efficiently convey information about the swarm's current state, its future states, and the effects of human input on its behavior. This work originates from the recent key contributions to human-swarm interaction [5,[9][10][11][12][13][14] and the use of nonverbal communication from robots [15][16][17][18][19]. Both domains are discussed in this section, leading to the key concept of the cohesion of a swarm for group-level perception of motion.…”
Section: Expressive Behavior Of Robotic Swarmsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important issue for the supervision of a semiautonomous swarm is the possibility to efficiently convey information about the swarm's current state, its future states, and the effects of human input on its behavior. This work originates from the recent key contributions to human-swarm interaction [5,[9][10][11][12][13][14] and the use of nonverbal communication from robots [15][16][17][18][19]. Both domains are discussed in this section, leading to the key concept of the cohesion of a swarm for group-level perception of motion.…”
Section: Expressive Behavior Of Robotic Swarmsmentioning
confidence: 99%
“…Yet more abstract, highlevel motion patterns can contribute to the emotional expression, without requiring a humanoid appearance, or even specific emotions to be expressed [27]. For instance, the kinematics of movement has been shown to participate in the emotional appraisal of an action [18,28]. Motion characteristics such as path curvature and acceleration are correlated with different levels of perceived arousal and valence [19,29].…”
Section: Nonverbal Communication In Hsimentioning
confidence: 99%
“…Other examples include Levillain et al [47], who investigated visitors' interaction and observation behaviors with mobile pianos in a museum. St. Onge et al [70] and St. Onge and Reeves [71] studied flying cubes in multiple publicly accessible spaces where flying cubes play the role of living creatures. In the work of Cuan et al [20], roboticists collaborated with a professional dancer to design interactive dancing robots.…”
Section: One-to-one Hri In Natural Settings Without Learningmentioning
confidence: 99%
“…The authors of [36] designed vision-based PID controllers for blimp to track human face. In [37], the authors investigated the control for a cubic shape blimp, where the PID controller and the Computed torque controller were presented. However, the influence of external disturbances was not analyzed for those mentioned controllers in [37].…”
Section: Related Workmentioning
confidence: 99%
“…The robot dynamic model linking the accelerations, the forces and moments acting on it can be derived by the Newton-Euler equations of motion [38,39]. However, due to the fact that the blimp robot is a robot whose density is close to the air, its dynamics is similar to that of underwater vehicles, the added-inertia effects are taken into account [37]. It is shown that the 6-DOF (degrees of freedom) nonlinear dynamic equations of the blimp motion can be expressed in F b as [38]…”
Section: Dynamic Modelmentioning
confidence: 99%